2016
DOI: 10.1007/s00426-016-0756-3
|View full text |Cite
|
Sign up to set email alerts
|

Intrusive thoughts: linking spontaneous mind wandering and OCD symptomatology

Abstract: One recent line of research in the literature on mind wandering has been concerned with examining rates of mind wandering in special populations, such as those characterized by attention-deficit/hyperactivity disorder, dysphoria, and schizophrenia. To best conceptualize mind wandering in studies examining special populations, it has recently been suggested that researchers distinguish between deliberate and spontaneous subtypes of this experience. Extending this line of research on mind wandering in special po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
118
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 22 publications
13
118
0
Order By: Relevance
“…In addition, in Study 2, we found that people reported a significant (non-zero) number of mind-wandering episodes that were intentionally engaged but lacking meta-awareness, as well as a significant (non-zero) number of episodes that were unintentionally engaged but (at least at some point) associated with meta-awareness. Thus, the present findings indicate that not only are meta-awareness and intentionality unique dimensions, but moreover, that there is indeed good reason for researchers to index the intentionality of mind wandering in future studies, as recently suggested (Seli, Risko, & Smilek, 2016b; Seli et al, 2016). …”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In addition, in Study 2, we found that people reported a significant (non-zero) number of mind-wandering episodes that were intentionally engaged but lacking meta-awareness, as well as a significant (non-zero) number of episodes that were unintentionally engaged but (at least at some point) associated with meta-awareness. Thus, the present findings indicate that not only are meta-awareness and intentionality unique dimensions, but moreover, that there is indeed good reason for researchers to index the intentionality of mind wandering in future studies, as recently suggested (Seli, Risko, & Smilek, 2016b; Seli et al, 2016). …”
Section: Discussionsupporting
confidence: 79%
“…However, at face value, the dimensions of intentionality and meta-awareness appear to share considerable overlap, and there remains the possibility that they may even be completely redundant. If this were the case, then it would suggest – contrary to recent claims (Seli, Risko, & Smilek, 2016b; Seli et al, 2016) – that researchers ought not to concern themselves with the intentionality dimension of mind wandering because it would provide no unique information beyond the meta-awareness dimension. If, on the other hand, there were evidence to suggest that these two dimensions are distinct, then this would provide support for the view that both dimensions ought to be considered in theoretical accounts of the wandering mind.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Not only have many researchers considered such scenarios to reflect mind wandering (e.g., Golchert et al, 2017;Forster & Lavie, 2009;Phillips, Mills, D'Mello, & Risko, 2016;Seli, Risko, & Smilek, 2016b; for a review, see Seli, Risko, Smilek, & Schacter. 2016), but moreover, the viability of assuming that participants' reports of "mind wandering" uniformly lack intention has been brought into question by recent work that has shown that people often report engaging in "intentional mind wandering" in their daily lives (e.g., Seli, Risko, Purdon, & Smilek, 2016;Seli, Smallwood, Cheyne, & Smilek, 2015).…”
Section: The Intentionality Of Mind Wanderingmentioning
confidence: 99%